The evolution of rice Brazilian exports and its competitiveness face on Mercosur countries (Research, Society and Development, 2021)
The opening of the Southern Common Market, called Mercosur, brought profound changes to the production and marketing of Brazilian agricultural products. In the case of rice, for instance, domestic production began to be replaced by imports of cereal produced in the other countries with lower prices. This made the country need to look for new markets to be able to sell the surplus of its production. This scenario brought problems for Brazilian rice producers as the cost to produce in other Mercosur countries is lower. Faced with this problem, the objective of this study was to analyze how Brazilian rice exports behaved over the years, its competitiveness in relation to Mercosur countries. To achieve this objective, descriptive statistical studies of exports from Brazil were carried out with the creation of graphs and tables using Microsoft Excel ® software. Subsequently, a competitiveness study was carried out comparing indices in Brazil with Mercosur countries. Three indexes were used: the Revealed Comparative Advantage Index (IVCR), Coverage Rate (TC) and the Regional Orientation Index (IOR). The results showed that Brazil evolved a lot in rice exports and improved the competitiveness of its product. Despite this fact, it still has lower rates than all the countries that were compared in the study.